IoT Based Monitoring and Alert System for Sewage Worker’s Safety - B, Subarna; P, Kaviya Shri J; C, Roshika; R, Sarulatha; Suresh, K (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Sewage system maintenance is a cumbersome task that has to be carried out properly since it is inevitable. Fatality occurs every year due to improper and inadequate facilities available as well as dangerous gases emitted during sewage disposal. Sewage workers are unaware of the dangers posed by a sudden attack of poisonous gases since these gases are odourless and if exposed for a prolonged period of time might lead to respiratory issues. To deal with this issue, an effective sewage monitoring and alert system is required. The proposed project continuously monitors the poisonous gases and oxygen present in sewage as well as the sanitation workers’ health. This effectively reduces the impact of the poisonous gases on the sewage worker.